2012
DOI: 10.1021/jm3006004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of 2,4-Dinitroaryldithiocarbamate Derivatives as Novel Monoacylglycerol Lipase Inhibitors

Abstract: Monoacylglycerol lipase (MAGL) is responsible for signal termination of 2-arachidonoylglycerol (2-AG), an endocannabinoid neurotransmitter endowed with several physiological effects. Previously, we showed that the arylthioamide scaffold represents a privileged template for designing MAGL inhibitors. A series of 37 compounds resulting from pharmacomodulations around the arylthioamide template were synthesized and tested to evaluate their inhibitory potential on MAGL activity as well as their selectivity over fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…175 Moreover, the modification of the amide moiety and the introduction of the sulfur atom appended to the thioamide group was performed based on an arylthioamide scaffold. 176 Especially, compounds 159 (CK16) and 160 The different effects on the alteration of 2-AG levels could be attributed to the differences in stability of 159 and 160. 176 Dilution studies indicated that 160 might covalently and irreversibly inactivate MAGL.…”
Section: Other Magl Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…175 Moreover, the modification of the amide moiety and the introduction of the sulfur atom appended to the thioamide group was performed based on an arylthioamide scaffold. 176 Especially, compounds 159 (CK16) and 160 The different effects on the alteration of 2-AG levels could be attributed to the differences in stability of 159 and 160. 176 Dilution studies indicated that 160 might covalently and irreversibly inactivate MAGL.…”
Section: Other Magl Inhibitorsmentioning
confidence: 99%
“…176 Especially, compounds 159 (CK16) and 160 The different effects on the alteration of 2-AG levels could be attributed to the differences in stability of 159 and 160. 176 Dilution studies indicated that 160 might covalently and irreversibly inactivate MAGL. 176 In 2009, two natural terpenoids 161 (pristimerin) and 162 (euphol) ( Figure 58) were reported to inhibit MAGL at submicromolar concentrations (IC50 = 0.093 and 0.315 µM, respectively).…”
Section: Other Magl Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to optimize the reaction condition, as a model reaction, aniline (1 mmol) was homogenized by mixing 0.8 g of Fe 3 O 4 @SiO 2 -SO 3 H and 0.2 mL water into a mortar with a ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 6 pestle until the aniline had disappeared as monitored by TLC. Then sodium nitrite (2 mmol) was added with continues grinding; the diazotation proceeded in few minutes and stable phenyldiazonium nano-magneto silica sulfate was prepared (Scheme 1, step 1).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] The formation of a carbon-sulfur (C-S) bond is a fundamental approach to introduce sulfur into organic compounds. Traditionally, various metal-based catalysts in combination with different ligands are generally used for the C-S bond formation by cross coupling of their halides.…”
Section: Introductionmentioning
confidence: 99%